Role of antibiotic in bronchiolitis management (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: Bronchiolitis is the most common illness among the patients attending the outpatient departments of CMH. It is predominantly a viral disease affecting the infants and young children. Though Antibiotic has little role, pediatricians frequently use them during bronchiolitis management. Very few randomized control trials without antibiotics in the management of bronchiolitis have so far been done. Objectives: To evaluate the outcome of bronchiolitis with or without antibiotics in a hospital setting. Methods: This prospective randomized control study was done in CMH Savar, during six months from October 2012 to March 2013. All the children below two years admitted in CMH Savar with first attack of Clinical Bronchiolitis were our study population. Exclusion criteria were: (i) atopic condition, (ii) congenital heart disease and/or (iii) known immunodeficiency. Study cases were randomly assigned into one of the two groups, AB group (Erythromycin/Amoxycilin) and NAB group (No Antibiotic).The NAB group was considered as control group. Supportive treatment was given according to the national guideline for management of bronchiolitis. Presenting symptoms and signs were followed-up twice daily while hospitalized and 7 days after discharge to determine the progress of disease. 70 JAFMC Bangladesh. Vol 9, No 2 (December) 2013 Outcome was determined by the progress of the variables in the structured follow-up format. Permission of commanding officer CMH Savar and verbal consent of the parents were taken before the study. Results: Fifty-four cases who could be followed up till after seven days of discharge were finally included in the study. Among them about half (25/54) received oral or intravenous antibiotic while rest (29/54) received only supportive therapy but no antibiotic (NAB group). Most of the cases were below six months of age. Male were about double of the female (37:17). The presenting features were cough, wheeze, fever and feeding difficulty. Clinical features of both groups progressed similarly in both the groups. With the given treatment 24 (96%) cases from AB group and 27 (93%) cases from NAB group improved and were discharged safely. 01 from AB and 02 from NAB group deteriorated and were then treated with broad spectrum antibiotics. There was no death. Mean hospital stay of AB group (5.6 days) was little longer than NAB group (4.2 days) and 16% (4/25) of them had respiratory symptoms at seven days follow up, but the difference of outcome between the two groups was not statistically significant. Conclusion: Antibiotics have no role in acute bronchiolitis management. DOI: http://dx.doi.org/10.3329/jafmc.v9i2.21833 Journal of Armed Forces Medical College Bangladesh Vol.9(2) 2013